Desigualdades de remuneraç\~ao entre egressos dos cursos de graduaç\~ao em ciências, tecnologias, engenharias e matemática (CTEM) - Luiz Carlos Zalaf Caseiro; Aguinaldo Nogueira Maciente (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This article investigates the factors associated with income inequalities among a cohort of graduates from Brazilian courses in science, technology, engineering, and mathematics (STEM) in 2011, over a period of seven years after graduation. It analyses how the social origins of these individuals are mediated by the characteristics of higher education courses and institutions in their effects on labor income inequalities. To do so, various administrative records from the federal government, with a focus on educational and employment data, were cross-referenced, and indicators of the prestige and quality of the courses and higher education institutions were constructed. In addition to descriptive analyses of the employment trajectories of STEM graduates, multilevel regression models were used to estimate the effects of social origins and higher education on their remuneration. The results indicate the following: i) the influence of higher education on income inequality among STEM graduates is substantial but decreases over time; ii) the effects of social origins, gender, and race on income inequality are partially mediated by the trajectory in higher education; iii) this mediation is higher for parental education and lower for gender, highlighting both the role of education in reducing social inequalities and the discriminatory mechanisms inherent in the labor market, which persist despite individuals' educational trajectories; iv) indicators of institutional quality and prestige have significant effects on graduates' remuneration, and they can even fully absorb the effect of public institutions on income, indicating their potential for analyzing the heterogeneity of the higher education system; and v) the economic cycle played a strong influence on the occupational integration of graduates, and the type of employment obtained immediately after graduation is important for job quality in the medium term.
Keywords: I23; I26; J31; J62; 330; higher education; returns to education; wage differentials; job; occupational and intergenerational mobility; STEM fields